Trashumancia, Espacio para Poesía y Arte : septiembre-octubre 1995 - Ocaranza, Jorge Octavio (dirección); Orendain, Jorge (coordinación) (Trashumancia, 1995)
Contiene obra de: Odön von Horváth, Josué Valencia García, Jorge Bustamante García, Elizabeth Flores, Cecilia Eudave, Jorge Octavio Ocaranza, Gary Snyder, Leonardo da Jandra, César López Cuadras, Alejandro Cruz Martínez, Amira Martínez Cruz, Antonio López Pérez, Esteban Ríos, Eva León, Filadelfo Figueroa, Jorge Margariño, Macario Matus, Olinka Villanueva, Carlos E. Bustos, David Magaña, Margarita Valdivia, Ricardo Sigala, Alexandro Bustos, Javier España, Octavio Romero, Zelene Bueno y Raúl Acosta.